Die beroepspatroon van verpleegkundiges - G.J. Cilliers (AOSIS, 1983)
A long-term study on the career pattern of registered nurses in South Africa is being undertaken by the HSRC. Significant findings in the second phase of the project include the fact that the years of working experience of the study group were relatively high compared to other dominantly female professions. No significant trend regarding loss of registered nurses over a number of years was found. Reasons why nurses leave and return to the profession were also investigated. Nurses mainly leave the profession because of family commitments and interest in nursing is a significant factor in motivating nurses to return.